The use of pentoxifylline in male reproduction abnormalities - Aamir Jalal Al-Mosawi (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2021)
Pentoxifylline a derivative of methylxanthine and nonspecific inhibitor of the phosphodiesterase with vasodilatory properties and rheological properties on blood that made it useful in the treatment of intermittent claudication. Pentoxifylline also has an immunomodulatory effect which inhibits inflammatory cytokines including tumor necrosis factor-alpha. The aim of this paper is to review the uses of pentoxifylline in male reproduction abnormalities.